EFFECT OF SOWING DATES AT GDD AND CROP GROWTH OF THREE SUNFLOWER (Genotypes Helianthus annuus L. ) - الشماع ليث; بكر رعد (Iraqi Journal of Science, 2024)
A field trial was conducted at Abu-Ghraib research station , Baghdad, Iraq , during the spring season of 2001 , The objectives were to study the effect of sowing dates on the performance of three sunflower genotypes . A split-plot lay in a randomized complete block design with three replications were used . Five sowing dates ( 16th Jan , 4th , 14th and 26th of Feb. and the 15th of March ) were assigned to main plots , where as genotypes in sub-plots . The first sowing date was the highest in growth from flowering to maturity and from emergency to maturity . The fifth sowing date plants need more GDD. Growing degree – day from emergency to flowering and the fifth sowing date did not varied significant from first and second sowing dates from sowing to maturity . The first sowing date plants need more GDD at the period from emergency to flowering , and not varied significantly with second sowing date in GDD .from end flowering to maturity . Euroflor genotype was the highest in growth from emergency to flowering . Pan7392 and Euroflor needs more GDD for the period from sowing to flowering .,and Manon genotype needs highest GDD from the end of flowering to maturity. The genotype Pan7392 need the highest GDD from sowing to maturity. Interaction between genotypes and sowing dates were also detected. Euroflor at the first sowing date had the highest GDD from emergency to flowering and Manon at second sowing date the highest growth from flowering to maturity and from emergency to maturity. Pan7392 at first sowing date need more GDD from other tow genotypes from flowering to maturity , Pan7392at first sowing date needs to maturity with the highest GDD.